Theory and explanation in social psychology - Gawronski, Bertram; Bodenhausen, Galen V. (The Guilford Press, 2015)
"This volume provides the first authoritative explication of metatheoretical principles in the construction and evaluation of social-psychological theories. Leading international authorities review the conceptual foundations of the field's most influential approaches, scrutinizing the range and limits of theories in various areas of inquiry. The chapters describe basic principles of logical inference, illustrate common fallacies in theoretical interpretations of empirical findings, and outline the unique contributions of different levels of analysis. An in-depth look at the philosophical foundations of theorizing in social psychology, the book will be of interest to any scholar or student interested in scientific explanations of social behavior. "--
Includes bibliographical references and index
Keywords: Aufsatzsammlung; Theoriebildung; Sozialpsychologie